Pembuatan Diorama Gerhana Matahari Sebagai Alternatif Media Pembelajaran IPA - Irman Muliadi; Salwa Salwa; Elza Rosmiatin Nafiz (Indonesian, 2024)
The Science materials on astronomy, particularly solar eclipses, are often perceived as abstract by junior high school students because the objects of study cannot be directly presented in the classroom. The limitations of two-dimensional (2D) media lead to low conceptual understanding and scientific literacy. This study aims to develop a solar eclipse diorama as an economical and interactive alternative for science learning media. The research method employed is Research and Development (R&D) using the 4D model (Define, Design, Develop, Disseminate). The research was conducted up to the Develop stage, limited to product functionality testing without extensive field trials. The research subjects involved an analysis of the characteristics of junior high school students in the transition from concrete to formal operational stages. The results showed that the diorama developed using styrofoam, wire, and LED lights effectively visualized the relative positions of the Earth, Moon, and Sun and the formation of umbra and penumbra shadows. The diorama functions well in simulating earth rotation, the lunar revolution, and the eclipse phenomena. This study concludes that the solar eclipse diorama is suitable for use as a practical and efficient alternative learning medium, especially for schools with limited laboratory facilities, to increase students' interest and conceptual understanding.